POSSIBILITY OF USING MACHINE LEARNING ALGORITHMS TO MODERNIZE AGRICULTURAL RESEARCH IN INDONESIA - Arianto Muditomo; Syamsari Syamsari (Journal of Agricultural and Rural Economy, 2023)
Even though many researchers and campuses have agricultural technology study programs, various technological and agricultural research in Indonesia still needs to be fully integrated. The author believes that technological advancements, particularly in Artificial Intelligence and Machine Learning, provide substantial advantages in various industries, including agriculture. This paper will examine the opportunities for using machine learning algorithms in precision agricultural research to inspire Indonesian agricultural researchers.